Properties of hybrid fiber reinforced concrete under repeated impact loads - Yildirim, S. Taner; Ekinci, Cevdet E.; Findik, Fehim (Pleiades Publishing Inc, 2010)
Steel, glass and polypropylene fiber reinforced concrete structures were investigated under repeated impact loads in this study. Twelve different concrete series prepared fiberless the one of all and the others reinforced polypropylene, glass, steel and hybrid fiber were produced. The polypropylene fibers in diameter of 50 mm, l/d (length/diameter) ratio of 400, glass fibers in diameter of 14 mm, l/d ratio of 857 and steel fibers in diameter of 0.75 mm, l/d ratio of 80 were used in concrete mixtures. The volumetric contents were 0.5, 0.75 and 1% in fiber reinforced concrete. The volumetric content was 0.1% in polypropylene and glass fiber reinforced concrete. Drop-weight test similar the method presented ACI 544.2R-89 was conducted using 28 days cured samples having dimensions of 100 x 100 x 100 mm and reduction of strength were determined by ultrasonic pulse velocity (UPV) test. Furthermore, initial crack formation and fracture numbers variation in samples were detected. In the present study, it was aimed to develop performance under repeated impact loads using fibers in concrete. As a result, especially impact performance was rather increased in steel fiber reinforced concrete, and hybrid fibers had also positive effect on the performance of concrete.
Keywords: Steel; glass and polypropylene fiber; hybrid fibered concrete; drop-weight test; repeated impact loads